Pengaruh Pendampingan Orang Tua Terhadap Perkembangan Sosial Emosional Anak di BA Aisyiyah Ponorogo - Fadhlina, Febriana Ahda; Artha, I Ketut Atmaja Johny (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Early childhood is the initial stage of human development. Parents have an important role in providing assistance during the child's development period. Mentoring is needed to achieve optimal child development, one of which is social emotional development. The creation of a comfortable and safe environment and the frequency of intense assistance by parents can support children's social emotional development. In this way, children become individuals who are able to recognize themselves and are sensitive to the environment. The aim of this research is to determine the effect of parental assistance on the social emotional development of children at BA Aisyiyah Keniten Ponorogo. The method used in this research is the quantitative research method. Data collection techniques use questionnaires. The number of respondents in this study was 15 respondents who were parents of BA Aisyiyah Ponorogo students. Data analysis was carried out using a simple linear regression test. The results of the simple linear regression test show that the calculated F value is 20.501 with a significance value of 0.00 < 0.05, so it can be stated that the parental assistance variable (X) has an influence on the child's social emotional development variable (Y). With this, H1 is accepted and Ho is rejected.